Ti3C2TxMXene / CuInSnS4 composite photocatalyst for photocatalytic methanation of carbon dioxide
By compounding the quality of TI3C2TX MXENE and Cuinsns4 by 1: 2, the efficient Ti3C2TX MXENE/CUINSNS4 composite photocatalyst is prepared, and the problem of poor production rate of single CUINSNS4 catalysts has been solved. The reaction shows good stability.
Patent Information
- Application Number
- CN202411500334.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The yield of a single CuInSnS4 catalyst is poor in photocatalyzing the reduction of carbon dioxide to methane.
The Ti3C2TX MXENE/Cuinsns4 composite photocatalyst is used to compound the Ti3C2TX MXENE powder with CUINSNS4 powder according to the quality ratio 1: 2 to prepare a composite catalyst with high electrical and improved optical catalytic activity.
The yield rate of photocatalytic carbon dioxide is increased, and the yield of methane can reach 48.51 μmol/g/h, and the composite catalyst shows good stability in the cycle experiment.
Smart Images

Figure CN119368209A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts for photocatalytic carbon dioxide methanation, and in particular to a Ti3C2T x MXene / CuInSnS4 composite photocatalyst. Background Art
[0002] With the acceleration of industrial progress, environmental pollution and energy consumption have become challenges faced by all mankind. Since Fujishima and Honda first demonstrated photoelectrocatalytic water splitting on photoactive semiconductor catalysts in 1972, people have been committed to developing efficient photocatalysts that can collect solar energy and convert it into chemical energy. Polymetallic chalcogenides are mainly composed of abundant and non-toxic elements on the earth. Due to their flexible composition, diverse structure and adjustable properties, they have application prospects in photocatalytic carbon dioxide reduction.
[0003] Copper indium tin sulfide (CuInSnS4) performs well in the photocatalytic reduction of carbon dioxide due to its unique crystal structure and optical properties. However, CuInSnS4 crystals tend to agglomerate during the preparation process, and photogenerated electrons and holes are prone to recombination, resulting in limited activity in the photocatalytic methanation of carbon dioxide.
[0004] MXene materials were first discovered by Professor Yury Gogotsi and Professor Michel Barsoum of Drexel University in the United States in 2011. Due to the presence of hydroxyl groups or terminal oxygen on the surface of MXene materials, they have the metallic conductivity of transition metal carbides. MXene has a wide range of application potentials in electrochemical energy storage, sensors, catalysis, etc. due to its high conductivity, adjustable work function, good light transmittance, and easy composite properties with other materials. Summary of the invention
[0005] The problem in the prior art is that the single CuInSnS4 catalyst has a poor yield in the photocatalytic reduction of carbon dioxide to methane. x MXene / CuInSnS4 composite photocatalyst, the preparation method thereof comprises the following steps:
[0006] (1) Lithium fluoride is fully dissolved in concentrated hydrochloric acid, and then Ti3AlC2 powder is added to the concentrated hydrochloric acid, and the reaction is stirred until the aluminum layer in the Ti3AlC2 layered structure is completely etched away. After the reaction is completed, the obtained solid product is washed with deionized water until the filtrate becomes neutral, and the obtained solid product is dispersed in deionized water, and ultrasonically dispersed uniformly under the protection of an inert atmosphere, and the obtained dispersion is subjected to solid-liquid separation to obtain a solid product, and then freeze-dried to obtain Ti3C2Tx MXene powder;
[0007] (2) adding cuprous chloride, tin tetrachloride pentahydrate and indium trichloride tetrahydrate into deionized water, stirring and dispersing them uniformly, then adding thioacetamide as a sulfur source into the above dispersion, dispersing and stirring them uniformly, placing the mixture in a reactor for high-temperature hydrothermal reaction, and after the reaction is completed, washing the obtained product with deionized water and drying it to obtain CuInSnS4 powder;
[0008] (3) Ti3C2T x MXene powder and CuInSnS4 powder were uniformly dispersed in deionized water to obtain Ti3C2T x MXene powder solution and CuInSnS4 powder solution, while ultrasonically mixing Ti3C2T x The MXene powder solution was added dropwise into the CuInSnS4 powder solution to obtain a mixed solution. After the addition was completed, the solution was evenly dispersed by ultrasonication, and then stirred for reaction for no less than 8 hours. The obtained reaction solution was collected by solid-liquid separation to obtain a solid product. The obtained solid product was dried to obtain Ti3C2T x MXene / CuInSnS4 composite photocatalyst;
[0009] The mixed solution contains Ti3C2T x The mass ratio of MXene powder to CuInSnS4 powder is 1:2.
[0010] Preferably, in step (2), the mass ratio of cuprous chloride to tin tetrachloride pentahydrate, indium trichloride tetrahydrate, and thioacetamide is (0.095-0.01):(0.345-0.355):(0.29-0.30):(0.37-0.38)
[0011] Preferably, the temperature of the high-temperature hydrothermal reaction in step (2) is 170-190° C., and the hydrothermal reaction time is 22-26 h.
[0012] Preferably, the concentration of concentrated hydrochloric acid in step (1) is 8-10M.
[0013] The present invention has the following beneficial effects:
[0014] (1) The preparation method of the present invention is simple and easy to implement, and the preparation conditions are easy to control. x The addition of MXene enhances the conductivity of the composite material and inhibits the recombination of photogenerated electrons and holes to a certain extent, which is more conducive to the photocatalytic carbon dioxide reduction methanation reaction;
[0015] (2) The present invention found through experiments that after Ti3C2Tx MXene powder and CuInSnS4 powder are compounded in a mass ratio of 1:2, the obtained Ti3C2Tx MXene / CuInSnS4 composite photocatalyst has the best photocatalytic effect, and the methane yield can reach 48.51 μmol / g / h. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 : Ti3C2T prepared in Example 2 x MXene, CuInSnS4, Ti3C2T x XRD diffraction comparison diagram of MXene / CuInSnS4 composite photocatalyst.
[0017] Figure 2 : SEM image of 2-MXene / CuInSnS4 composite photocatalyst.
[0018] Figure 3 : MXene, CuInSnS4 and 2-Ti3C2T obtained in Example 2 x Comparison chart of the effects of MXene / CuInSnS4, 1-MXene / CuInSnS4 and 3-MXene / CuInSnS4 used for photocatalytic carbon dioxide methanation reaction.
[0019] Figure 4 : Comparison of the test results of photocatalytic carbon dioxide reduction cycle experiments on MXene, CuInSnS4 and 2-MXene / CuInSnS4 obtained in Example 2. DETAILED DESCRIPTION
[0020] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0021] Example 1
[0022] (1) Ti3C2T x Preparation of MXene powder
[0023] 2.0 g of lithium fluoride was dissolved in 25.7 mL of hydrochloric acid (9 M), stirred in an oil bath at 40 ° C for 15 min, then 1.5 g of Ti3AlC2 powder was added, stirred and reacted for 48 h, and then the reaction solution was washed with deionized water until the supernatant was neutral. The obtained solid product was dispersed in deionized water and ultrasonically dispersed under argon for 3 h. The solid product was then collected by centrifugation and freeze-dried to obtain Ti3C2T x MXene powder;
[0024] (2) Preparation of CuInSnS4
[0025] 0.099 g of cuprous chloride, 0.35 g of tin tetrachloride pentahydrate and 0.293 g of indium trichloride tetrahydrate were added to 40 mL of deionized water and stirred evenly. Then, 0.375 g of thioacetamide was added and stirred evenly. Subsequently, the solution was transferred to a reactor and sealed. The reaction was carried out at 180° C. for 24 h. After natural cooling, the product was centrifuged. The obtained solid product was washed with deionized water and vacuum dried at 60° C. overnight to obtain CuInSnS4 powder.
[0026] (3) Ti3C2T x Preparation of MXene / CuInSnS4 composite photocatalyst
[0027] 0.02g Ti3C2T x MXene powder and 0.02 g CuInSnS4 powder were dissolved in 40 mL deionized water respectively and ultrasonically dispersed for 30 min. After being uniformly dispersed, the MXene aqueous solution was added dropwise to the CuInSnS4 solution while ultrasonicating. The mixed solution was ultrasonically dispersed for another 1 h and then stirred for another 8 h. The solid product was collected by centrifugation and dried in vacuum at 60 °C to obtain Ti3C2T4 x MXene / CuInSnS4 composite photocatalyst (denoted as 1-MXene / CuInSnS4).
[0028] Example 2 is the same as Example 1, except that the amount of CuInSnS4 powder added in step (3) of Example 2 is 0.04 g. The composite photocatalyst obtained in Example 2 is denoted as 2-MXene / CuInSnS4.
[0029] Example 3 is the same as Example 1, except that the amount of CuInSnS4 powder added in step (3) of Example 3 is 0.06 g. The composite photocatalyst obtained in Example 3 is recorded as 3-MXene / CuInSnS4.
[0030] Ti3C2T prepared in Example 2 x MXene, CuInSnS4, Ti3C2T x The crystal structure of MXene / CuInSnS4 composite photocatalyst was analyzed by Rigaku D / max2500PC rotating X-ray diffractometer, where the X-ray was Cu target Kα Voltage 40kV, current 100mA, step length 0.02°, scanning range 5~80°. X-ray diffraction spectrum is as attached in the manual Figure 1 As shown, Ti3C2T xBoth MXene and CuInSnS4 have strong diffraction peaks, and CuInSnS4 matches well with its standard card (PDF#29-0548), proving that Ti3C2T x MXene and CuInSnS4 were successfully synthesized. Meanwhile, Ti3C2T x The MXene / CuInSnS4 (corresponding to MCISS in the figure) composite photocatalyst can be seen to be Ti3C2T x The characteristic peaks of the (002) crystal plane of Ti3C2T4 and CuInSnS4 are also present. x MXene / CuInSnS4 composite materials were successfully synthesized.
[0031] The Ti3C2T obtained in Example 2 was observed using a Japanese JSM-6360A scanning electron microscope. x The scanning electron microscopy of 2-MXene / CuInSnS4 with a mass ratio of MXene powder to CuInSnS4 powder of 1:2 is shown in the attached manual. Figure 2 As shown in the figure, it can be seen that CuInSnS4 nanocrystals are loaded on the flake Ti3C2T x MXene surface.
[0032] The MXene, CuInSnS4 and 2-Ti3C2T prepared in Example 2 were x MXene / CuInSnS4 (corresponding to MCISS (1:2) in the figure), 1-MXene / CuInSnS4 (corresponding to MCISS (1:1) in the figure), and 3-MXene / CuInSnS4 (corresponding to MCISS (1:3) in the figure) composite materials are used as photocatalysts for photocatalytic carbon dioxide reduction methanation reaction, and the performance of photocatalytic carbon dioxide methanation of different photocatalysts is tested respectively. The specific test steps are as follows:
[0033] 6 mg of photocatalyst was dissolved in 2 mL of deionized water, and ultrasonically mixed. The catalyst solution was then dripped onto the upper surface of a clean glass sheet using a rubber-tipped dropper, and the water was dried at 70°C. Place a glass sheet with catalyst dispersed on it at the opening of a small beaker, take a transparent glass reactor with only one air inlet and two air outlets on the top (when the air inlet and the air outlet are all closed, the inside of the reactor is sealed, and the volume of the reactor is 370 mL), and put 20 mL of aqueous solution at the bottom of the reactor. Take a small beaker with a range of 25 mL and place it inside the reactor, and place the glass sheet sample horizontally at the opening position at the top of the small beaker, with the side of the glass sheet sample with the photocatalyst loaded facing up, close one of the air outlets of the reactor, and open the other air outlet, continuously introduce high-purity CO2 gas from the air inlet, and exhaust the air in the reactor from the opened air outlet. This process lasts for 15 minutes. At this time, the ventilation ends, the air intake and exhaust are stopped, and then the xenon lamp above the reaction is turned on, and the light shines through the transparent container cover on the top of the reactor to irradiate the small beaker in the reactor, with an irradiation power of 300 W. After 4 hours of illumination, the gas in the reactor was extracted from one of the gas outlets using a syringe and injected into a gas chromatograph for gas composition and content determination. The yields of CH4 and CO were calculated from the CH4 and CO peak areas obtained by chromatographic analysis (yield calculation formula: V = [(S / 40.663) × (0.001127232 / m) × 350 × 2] / t. Where S: CH4 or CO peak area obtained by chromatographic analysis, m: mass of photocatalyst, t: illumination time)
[0034] The experimental results are as shown in the attached manual. Figure 3 As shown in the figure, the CO production rates of pure MXene and CuInSnS4 are 4.29 and 2.24 μmol / g / h, respectively, and the CH4 production rates of pure MXene and CuInSnS4 are 7.85 and 11.16 μmol / g / h, respectively. The CO production rate of the 2-MXene / CuInSnS4 composite photocatalyst is 18.92 μmol / g / h, which is about 4.4 and 8.4 times that of pure MXene and CuInSnS4, and the CH4 production rate of the 2-MXene / CuInSnS4 composite photocatalyst is 48.51 μmol / g / h, which is about 6.4 and 4.3 times that of pure bismuth oxybromide and zinc oxide. It can be seen that the composite of MXene and CuInSnS4 can effectively improve the photocatalytic carbon dioxide reduction activity of the photocatalyst. The prepared Ti3C2T x MXene / CuInSnS4 composite photocatalyst has higher photocatalytic activity.
[0035] In order to verify the Ti3C2T prepared by the present invention xThe stability of the MXene / CuInSnS4 composite photocatalyst was tested by photocatalytic reduction of carbon dioxide to methane on the MXene, CuInSnS4 and 2-MXene / CuInSnS4 (corresponding to MCISS in the figure) prepared in Example 2. The specific test steps are as follows:
[0036] 6 mg of photocatalyst was dissolved in 2 mL of deionized water, and after ultrasonic mixing, the catalyst solution was dripped onto the upper surface of a clean glass sheet with a rubber-tipped dropper, and the water was dried at 70°C to obtain a glass sheet sample. A transparent glass reactor with only one air inlet and two air outlets on the upper part and a volume of 370 mL was taken, and 20 mL of aqueous solution was contained at the bottom of the reactor. A small beaker with a range of 25 mL was placed inside the reactor, and the glass sheet sample was placed horizontally at the top opening of the small beaker, with the side of the glass sheet sample loaded with photocatalyst facing upward. One of the air outlets of the reactor was closed, and the other air outlet was opened. High-purity CO2 gas was continuously introduced from the air inlet, and the air in the reactor was discharged from the open air outlet. This process was maintained for 15 minutes. At this time, the ventilation was terminated, and the air inlet and outlet were stopped. Then the xenon lamp above the reaction was turned on, and the light was irradiated to the small beaker in the reactor through the transparent container cover on the top of the reactor, with an irradiation power of 300 W. After 4 hours of illumination, the gas in the reactor was extracted from one of the gas outlets using a syringe and injected into a gas chromatograph for gas composition and content determination. The yields of CH4 and CO were calculated from the CH4 and CO peak areas obtained by chromatographic analysis (the test results correspond to the attached manual). Figure 4 4th).
[0037] After the test, scrape the photocatalyst on the glass sample and redisperse it in 2 mL of deionized water to obtain a catalyst solution. After ultrasonic mixing, use a rubber-tipped dropper to drop the catalyst solution onto the upper surface of a clean glass sheet, dry the water at 70°C, and obtain a glass sheet sample again. According to the above photocatalytic steps, the yields of CH4 and CO after irradiation for another 4 hours were tested (the test results correspond to the attached manual). Figure 4 8th).
[0038] After the test, the photocatalyst on the glass sample was scraped off again, and redispersed in 2 mL of deionized water to obtain a catalyst solution. After ultrasonic mixing, the catalyst solution was dripped onto the upper surface of the clean glass with a rubber-tipped dropper, and the water was dried at 70°C to obtain a glass sample again. The yields of CH4 and CO after irradiation for 4 hours were tested according to the above photocatalytic steps (the test results correspond to the attached manual). Figure 4 12th in the.
[0039] After the test, continue to scrape the photocatalyst on the glass sample, redisperse it in 2 mL of deionized water to obtain a catalyst solution, mix it evenly with ultrasound, and then drop the catalyst solution onto the upper surface of the clean glass with a rubber-tipped dropper. Dry the water at 70°C to obtain a glass sample again. Test the yield of CH4 and CO after irradiation for another 4 hours according to the above photocatalytic steps (the test results correspond to the attached manual). Figure 4 16th in the.
[0040] The experimental results are as shown in the attached manual. Figure 4 As shown, after 4 photocatalytic cycles, Ti3C2T x The CH4 yield of the MXene / CuInSnS4 composite photocatalyst was 43.66 μmol / g / h, which was only 10% lower than the first CH4 yield. x MXene / CuInSnS4 composite photocatalyst has good stability.
[0041] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. Ti3C2T for photocatalytic carbon dioxide methanation x MXene / CuInSnS4 composite photocatalyst, characterized by The yield of photocatalytic reduction of carbon dioxide to methane was significantly improved. The preparation method comprises the following steps: (1) Lithium fluoride is fully dissolved in concentrated hydrochloric acid, and then Ti3AlC2 powder is added to the concentrated hydrochloric acid, and the reaction is stirred until the aluminum layer in the Ti3AlC2 layered structure is completely etched away. After the reaction is completed, the obtained solid product is washed with deionized water until the filtrate becomes neutral, and the obtained solid product is dispersed in deionized water, and ultrasonically dispersed uniformly under the protection of an inert atmosphere, and the obtained dispersion is subjected to solid-liquid separation to obtain a solid product, and then freeze-dried to obtain Ti3C2T x MXene powder; (2) adding cuprous chloride, tin tetrachloride pentahydrate and indium trichloride tetrahydrate into deionized water, stirring and dispersing them uniformly, then adding thioacetamide as a sulfur source into the above dispersion, dispersing and stirring them uniformly, placing the mixture in a reactor for high-temperature hydrothermal reaction, and after the reaction is completed, washing the obtained product with deionized water and drying it to obtain CuInSnS4 powder; (3) Ti3C2T x MXene powder and CuInSnS4 powder were uniformly dispersed in deionized water to obtain Ti3C2T x MXene powder solution and CuInSnS4 powder solution, while ultrasonically mixing Ti3C2T x The MXene powder solution was added dropwise into the CuInSnS4 powder solution to obtain a mixed solution. After the addition was completed, the solution was evenly dispersed by ultrasonication, and then stirred for reaction for no less than 8 hours. The obtained reaction solution was collected by solid-liquid separation to obtain a solid product. The obtained solid product was dried to obtain Ti3C2T x MXene / CuInSnS4 composite photocatalyst; The mixed solution contains Ti3C2T x The mass ratio of MXene powder to CuInSnS4 powder is 1:
2.
2. The Ti3C2Tx MXene / CuInSnS4 composite photocatalyst for photocatalytic carbon dioxide methanation according to claim 1, characterized in that: In step (2), the mass ratio of cuprous chloride to tin tetrachloride pentahydrate, indium trichloride tetrahydrate and thioacetamide is (0.095-0.01):(0.345-0.355):(0.29-0.30):(0.37-0.38).
3. The Ti3C2Tx MXene / CuInSnS4 composite photocatalyst for photocatalytic carbon dioxide methanation according to claim 1, characterized in that: The temperature of the high temperature hydrothermal reaction in step (2) is 170-190° C., and the hydrothermal reaction time is 22-26 hours.
4. The Ti3C2Tx MXene / CuInSnS4 composite photocatalyst for photocatalytic carbon dioxide methanation according to claim 1, characterized in that: The concentration of concentrated hydrochloric acid in step (1) is 8-10M.
Citation Information
Patent Citations
Method for preparing spinel-structure compound nanocrystal
CN103979598A
Copper indium tin selenide / zinc selenide core-shell quantum dot and preparation method and application thereof
CN114591742A
Low-melting-point alloy composite material and composite material structure
US11795529B1
Method for fabricating copper / indium / gallium / selenium solar cell by wet process under non-vacuum condition
US20110189813A1
Cited By
Preparation method of double-nonmetal plasmon multifunctional interference material
CN120504321A
Spinel-based composite photocatalyst, preparation method and application of spinel-based composite photocatalyst in catalysis of CO2 conversion
CN121004007A